EDUCAÇÃO AMBIENTAL COMO FERRAMENTA PARA PROMOVER MUDANÇAS ORGANIZACIONAIS - ENVIRONMENTAL EDUCATION AS TOOL TO PROMOTE ORGANIZATIONAL CHANGES - Tatiane Barbosa Trindade; Anna Cristina Lanna (Revista Geográfica Acadêmica, 2007)
Paper Communication This article is intended to show the importance of investing in intensive programs of environmental education,so that it is a tool in the context of changing cultural, social and ethical within organizations.